Debtors' crisis or creditors' crisis? Who pays for the European sovereign and subprime mortgage losses? - Jan Kregel (Levy Economics Institute of Bard College, 2011)
In the context of the eurozone's sovereign debt crisis and the US subprime mortgage crisis, Senior Scholar Jan Kregel looks at the question of how we ought to distribute losses between borrowers and lenders in cases of debt resolution. Kregel tackles a prominent approach to this question that is grounded in an analysis of individual action and behavioral characteristics, an approach that tends toward the conclusion that the borrower should be responsible for making creditors whole. The presumption behind this style of analysis is that the borrower - the purportedly deceitful subprime mortgagee or supposedly profligate Greek - is the cause of the loss, and therefore should bear the entire burden.
Keywords: 330